Single Cell T Cell Receptor Sequencing: Techniques and Future Challenges - De Simone, Marco; Rossetti, Grazisa; Pagani, Massimiliano (Frontiers in Immunology, 2018)
The peculiarity of T cell is their ability to recognize an infinite range of self and foreign antigens. This ability is achieved during thymic development through a complex molecular mechanism based on somatic recombination that lead to the expression of a very heterogeneous population of surface antigen receptors, the T Cell Receptors or TCRs. TCRs are cell specific and represent a sort of “molecular tag” of T cells and have been widely studied to monitor the dynamics of T cells in terms of clonality and diversity in several contexts including lymphoid malignancies, infectious diseases, autoimmune diseases and tumor immunology. In this review, we provide an overview of the strategies used to investigate the TCR repertoire from the pioneering techniques based on the V segments identification to the revolution introduced by Next Generation Sequencing that allows for high-throughput sequencing of alpha and beta chains. Single cell based approaches brought the analysis to a higher level of complexity and now provide the opportunity to sequence paired alpha and beta chains. We also discuss novel approaches that through the integration of TCR tracking and mRNA single-cell sequencing offer a valuable tool to associate antigen specificity to transcriptional dynamics and to understand the molecular mechanisms of T cell plasticity.